Deficiency in CD4 T Cells Leads to Enhanced Postpartum Internal Carotid Artery Vasoconstriction in Mice: The Role of Nitric Oxide - Gokina, Natalia I.; Fairchild, Rebecca I.; Prakash, Kirtika; DeLance, Nicole M.; Bonney, Elizabeth A. (Frontiers in Physiology, 2021)
The risk of postpartum (PP) stroke is increased in complicated pregnancies. Deficiency in CD4 T cell subsets is associated with preeclampsia and may contribute to PP vascular disease, including internal carotid artery (ICA) stenosis and stroke. We hypothesized that CD4 T cell deficiency in pregnancy would result in ICA dysregulation. We characterized function, mechanical behavior, and structure of ICAs from C57BL/6 (WT) and CD4 deficient (CD4KO) mice, and assessed the role of NO in the control of ICA function at pre-conception and PP. WT and CD4KO mice were housed under pathogen-free conditions, mated, and allowed to litter or left virgin. At 3 days or 4 weeks PP, mice were euthanized. The responses to phenylephrine (PE), high K+ and acetylcholine (ACh) were assessed in pressurized ICAs before and after NOS inhibition. Passive lumen diameters were measured at 3-140 mmHg. eNOS and iNOS expression and T cell presence were evaluated by immunohistochemistry. Constriction of WT ICAs to PE was not modified PP. In contrast, responses to PE were significantly increased in ICAs from PP as compared to virgin CD4KO mice. Constriction to high K+ was not enhanced PP. ICAs from WT and CD4KO mice were equally sensitive to ACh with a significant rightward shift of dose-response curves after L-NNA treatment. NOS inhibition enhanced PE constriction of ICAs from WT virgin and PP mice. Although a similar effect was detected in ICAs of virgin CD4KO mice, no such changes were observed in vessels from PP CD4KO mice. Passive arterial distensibility at physiological levels of pressure was not modified at PP. ICA diameters were significantly increased in PP with no change in vascular wall thickness. Comparison of eNOS expression in virgin, 3 days and 4 weeks PP revealed a reduced expression in ICA from CD4 KO vs. WT PP vessels which reached significance at 4 weeks PP. iNos decreased PP in vessels from WT and CD4KO mice. Dysregulation of the CD4 T cell population in pregnancy may make ICA vulnerable to vasospasm due to decreased NO-dependent control of ICA constriction. This may lead to cerebral hypoperfusion and increase the risk of maternal PP stroke.